Postsocialism and Cultural Politics : China in the Last Decade of the Twentieth Century - Zhang, Xudong, 1965- (Book collections on Project MUSE., 2008)
A sequel to Zhang's Chinese Modernism, it discusses crucial issues in China in the 1990s including nationalism, neo-liberalism, postmodernism, nostalgia, revisionism and the intellectual formulations and cultural politics.